Recent Developments of USG Score for GCA - Helen Keen (Journal of Clinical Rheumatology and Immunology)
The 2022 European League Against Rheumatism (EULAR) guidelines have introduced a significant advancement in the diagnostic approach to Giant Cell Arteritis (GCA). According to these updated guidelines, Ultrasound (US) examinations of the cranial and axillary arteries should be considered the primary imaging method for evaluating patients who are suspected to have GCA, provided that the examinations are performed by adequately trained specialists using high-quality equipment. This recommendation marks a notable shift in the traditional management practices for GCA, as it acknowledges the effectiveness of ultrasound as a non-invasive, efficient, and reliable point-of-care test for individuals with suspected GCA. As a result, this development has paved the way for the establishment of fast-track clinics dedicated to GCA diagnosis and treatment across various parts of the globe. However, it is important to note that the use of ultrasound for diagnosing GCA comes with certain challenges. The highly technical nature of the ultrasound procedure, combined with its dependence on the expertise of the operator, often leads to criticism regarding its reliability as a clinical tool. This can create confusion among clinicians when they attempt to interpret formal ultrasound reports, especially if they are not trained in sonography themselves. In this presentation, we will thoroughly examine the evidence supporting the use of ultrasonography in the diagnosis of Giant Cell Arteritis. The discussion will encompass several key concepts, including: 1. The validity of ultrasonography as a diagnostic tool for GCA. 2. The diagnostic performance of ultrasound in identifying the condition. 3. The practical utility of ultrasound in an Australian Fast Track Clinic setting. 4. The assessment of treatment response and sensitivity to change, as measured by ultrasound findings. 5. The various scoring tools utilized in ultrasound evaluations, such as the Halo Count, the Halo Score, and the OMERACT GCA Ultrasound Score. 6. A review of the EULAR guidelines and how they have evolved over time. 7. Critical information that clinicians who are not trained in sonography need to understand regarding the use of ultrasound in GCA. Through this comprehensive review, we aim to clarify the role of ultrasonography in the diagnosis and management of Giant Cell Arteritis, empowering clinicians with the knowledge they need to effectively utilize this diagnostic tool in their practice.